2008
DOI: 10.1074/jbc.m705652200
|View full text |Cite
|
Sign up to set email alerts
|

Limited Mitochondrial Permeabilization Is an Early Manifestation of Palmitate-induced Lipotoxicity in Pancreatic β-Cells

Abstract: Involvement of the mitochondrial permeability transition (MPT) pore in early stages of lipotoxic stress in the pancreatic ␤-cell lines MIN6 and INS-1 was the focus of this study. Both long term (indirect) and acute (direct) effects of fatty acid (FA) application on ␤-cell susceptibility to Ca 2؉ -induced MPT induction were examined using both permeabilized and intact ␤-cells. Long term exposure to moderate (i.e. below cytotoxic) levels of the saturated FA palmitate sensitized ␤-cell mitochondria to MPT induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 105 publications
5
57
1
1
Order By: Relevance
“…At the same time, the INS-1 832/13 ␤-cells adapted to the exposure to palmitate by increasing their capacity to oxidize lipids. There is some disagreement with previous studies, which have shown increased respiration upon prolonged palmitate treatment (19,58). It should be kept in mind that we examined glucose-induced, not lipid-induced, respiration.…”
Section: Discussioncontrasting
confidence: 39%
“…At the same time, the INS-1 832/13 ␤-cells adapted to the exposure to palmitate by increasing their capacity to oxidize lipids. There is some disagreement with previous studies, which have shown increased respiration upon prolonged palmitate treatment (19,58). It should be kept in mind that we examined glucose-induced, not lipid-induced, respiration.…”
Section: Discussioncontrasting
confidence: 39%
“…The data suggest that changes in stearate-CoA or its metabolite levels control mineralization and osteogenic differentiation in vascular cells, through a mechanism yet to be determined. In a number of previous studies using cell culture systems, saturated fatty acids have been shown to have lipotoxic effects via several cell signaling pathways including 1) endoplasmic reticulum stress (36,37), 2) Toll-like receptor activation (38 -41), 3) an increase in reactive oxygen species (42, 43), 4) de novo ceramide synthesis (44 -46), 5) modification of mitochondrial structure and function (44,47), and 6) suppression of anti-apoptotic components (46,48). In addition, unsaturated fatty acid supplementation has been known to block the lipotoxic effects of saturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…5b) (as previously shown in Refs. 23,32,33). The combination of depolarization and reduced oxygen consumption suggested a respiratory chain defect.…”
Section: Palmitate Increases Ap Formation But Autophagy Does Notmentioning
confidence: 99%